IT usage, perceptions and literacy of medical students - Bulgiba, Awang; Noran, M.H. (SAGE Publications, 2003)
A cross-sectional study of medical students using a self-administered questionnaire was carried out in the Faculty of Medicine, University of Malaya, Malaysia from December 2000 to January 2001 to determine IT usage, perceptions and literacy of medical students. 366 of 653 (56.0) students reported owning some type of personal computer. Students mainly used the computer to get onto the Internet, do word-processing and make presentations. Junior (Year One and Two) students and those who had used computers before entering university were more likely to use the Internet. Those who own computers were more likely to feel comfortable with software (OR 1.61, 95 CI: 1.09, 2.38). Students who use the Internet were more likely to perceive that IT facilitated their studies (OR 4.61, 95 CI: 2.35, 9.05). The highest self-reported IT skill was e-mailing followed by surfing the World Wide Web and word-processing. Male students and junior students had significantly higher self-reported IT literacy scores compared to female students and senior students. Significant predictors for an IT identifier score after adjusting for other variables were self-reported rating of computer knowledge, number of siblings, parents' income and gender. Asia Pac JPublic Health 2003; 15(2): 127-134.